Peripheral blood eosinophils and other non‐invasive biomarkers can monitor treatment response in eosinophilic oesophagitis. Issue 9 (27th August 2015) - Schlag, C.; Miehlke, S.; Heiseke, A.; Brockow, K.; Krug, A.; von Arnim, U.; Straumann, A.; Vieth, M.; Bussmann, C.; Mueller, R.; Greinwald, R.; Bajbouj, M.
Summary Background Monitoring of the treatment response in eosinophilic oesophagitis (EoE) requires structured endoscopical and histological examination of the oesophagus. Less invasive methods would be highly desirable. Aim To evaluate the utility of several EoE‐associated blood and serum markers in order to non‐invasively monitor the response to treatment with swallowed topical corticosteroids in adult EoE patients. Methods In a randomised, controlled double‐blind trial blood samples of EoE patients (n = 69) were collected at baseline and after 14 days of treatment with budesonide (n = 51) or placebo (n = 18) respectively. Absolute blood eosinophil count (AEC) as well as serum levels of CCL‐17, CCL‐18, CCL‐26, eosinophil‐cationic‐protein (ECP) and mast cell tryptase (MCT) were determined and correlated with oesophageal eosinophil density and with symptom and endoscopy scores. Results Histological remission, defined as mean number of <16 eos/mm2 hpf at end‐of‐treatment, was achieved in 98% of the budesonide and 0% of the placebo recipients. AEC [380.2 vs. 214.7/mm3 (P = 0.0001)], serum‐CCL‐17 [294.3 vs. 257.9 pg/mL (P = 0.0019)], ‐CCL‐26 [26.7 vs. 16.2 pg/mL (P = 0.0058)], ‐ECP [45.5 ± 44.7 vs. 27.5 ± 25.0 μg/L (P = 0.0016)] and ‐MCT [5.3 ± 2.9 vs. 4.5 ± 2.6 μg/L (P = 0.0019)] significantly decreased under budesonide but not under placebo. AEC significantly correlated with oesophageal eosinophil density before (r = 0.28, P = 0.0236) and after (r = 0.42, P = 0.0004) budesonide treatment. In ROC‐AUC analyses post‐treatment values of AEC were significantly associated with histological remission (ROC‐AUC 0.754; 95% CI: 0.617–0.891; P = 0.0003). Conclusions The budesonide‐induced treatment response in EoE is mirrored by several blood and serum markers, and the absolute blood eosinophil count is the most valuable as it shows correlation with the oesophageal eosinophil density.